Pengaruh Reward dan Punishment Terhadap Motivasi Belajar Siswa Kelas IV Sekolah Dasar - Fitri, Yunika Rahmi; Ain, Siti Quratul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Reward and punishment are very important in motivating students because through reward and punishment students will become more confident and responsible with the tasks given. Reward and punishment are two contradictory words, however, the two things are interrelated. The purpose of this study was to determine how the influence of reward and punishment on the learning motivation of fourth-grade elementary school students. This type of research is quantitative. This study uses a random sampling technique, the research subjects are all fourth-grade students for the 2021/2022 academic year with a total student population of 92 students. The results of data processing shows that the independent variables (reward (X1) and punishment (X2)) simultaneously have a significant effect on the dependent variable of learning motivation (Y) this is indicated by the calculated F value of 44.722 which is greater than F table 2.69, meaning this causes Hi to be accepted.